Upstream Advanced. Students Book - Evans, Virginia and Edwards, Lynda (Newbury Express Publishing, 2009)
Upstream Advanced is a modular secondary-level course for learners of the English language at CEF C1 level. The series combines active English learning with a variety of lively presented in themed units.
Keywords: English Practice